FEATURES OF STREET-ROAD NETWORK MODERN DESIGNING AND RECONSTRUCTION IN CITIES - Lytvynenko, T. P.; Gasenko, L. V.; Sharyi, G. I. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The main problems associated with the organization of traffic and pedestrians movement in modern cities are determined. The world experience in designing and reconstruction the street-road network of cities is considered. The factors determining  current trends and features of designing and reconstruction of street-road network in Ukraine cities are identified. The priorities of street-road traffic affecing its formation and development are considered. The main goals to adap urban construction and reconstruction projects to the change of priorities, which took place in the theory of transport planning, are formulated.
Keywords: street-road network; transport planning; priorities of traffic; optimization of city planning structure